Is co-morbid depression adequately treated in patients repeatedly referred to specialist medical services with symptoms of a medical condition? - Sharpe, M; Burton, C; Sawhney, A; McGorm, K; Weller, D (2012)
Objective: Patients with a medical condition and co-morbid depression have more symptoms and use more medical services. We aimed to determine the prevalence of depression and the adequacy of its treatment in patients who had been repeatedly referred from primary to specialist medical care for the assessment of a medical condition. Methods: All patients who had at least three referrals to medical and surgical specialists for an assessment of symptoms attributed to a medical condition, over a five year period from five primary care practices in Edinburgh, UK were identified using a referral database and review of records. Participants were sent a questionnaire which included the PHQ-9 depression scale and additional questions about depression during the preceding 5. years. Details of treatment for depression were obtained from primary care records. Results: Questionnaires were sent to 230 patients and returned by 162 (70.4%). Forty-one (25.3%) had a PHQ-9 score of 10 or more and hence probable current depressive disorder. An additional 36 (22.2%) reported depression in the previous 5. years. Only eight (19.5%) of those reporting current depression and 20 (26%) of the 77 patients reporting previous depression had received minimally adequate treatment for it. Conclusion: Whilst we know that patients with medical conditions are often depressed and that such co-morbid depression is often undertreated, we have found that it is undertreated even in patients repeatedly referred to medical specialists. Better assessment and management of depression in such patients could both improve patients' quality of life and reduce the cost of care. © 2012 Elsevier Inc.